Identification and direction of changes in work-life balance dimensions in Visegrad Group countries - Marta Domagalska-Grędys; Adam Sagan; Katarzyna Piecuch (Entrepreneurial Business and Economics Review (EBER), 2025)
Objective: The article aimed to identify the dimensions and trajectories of work-life balance (WLB) across the Visegrad Group (V4) countries (Poland, the Czech Republic, Slovakia, and Hungary) during the period 2008- 2022. We posed two research questions: which factors are most responsible for WLB and how do the dimensions of WLB evolve over time among the V4 countries? Research Design & Methods: We employed a quantitative and interpretative approach. Based on statistical data, we identified WLB dimensions in the multiple factor analysis (MFA). The estimated factor values formed the basis for analysing the trajectories of changes in three indices (WORK, TIME, FAMILY) for each of the V4 countries over the 2009-2022 period. Findings: Among the three WLB dimensions, WORK was the most explanatory for WLB. The eigenvalue of the first dimension explained 32% of the total variance, the second dimension eigenvalue contributed 26% of the variance, and the third extracted dimension explained 15% of the total variance. We demonstrated the status of three WLB dimensions over a period of 14 years across the V4 countries. We found the greatest stabilization of WLB in the FAMILY dimension, while the WORK dimension distinctly differentiated the V4 countries. Although all V4 countries showed an increasing trend in the WORK index alongside a decrease in the TIME index, they clearly followed different paths in the development of WLB, including the pursuit of diversification (WORK), similarity (FAMILY), and the maintenance of stationarity (TIME). Implications & Recommendations: The findings may be valuable for planning future strategies aimed at enhancing the employees' WLB. Further research should focus, among other aspects, on the observation of WLB dimensions and the assessment of the trajectories identified in the article, including the impact of the V4 countries' decisions on the development of work-life balance policies. Contribution & Value Added: The number of studies on WLB has increased significantly over the past ten years, revealing the complexity of the phenomena and presenting diverse research perspectives. The proposed study approach based on multiple-factor analysis allowed us to capture the state of WLB in terms of its dimensions (WORK, TIME, FAMILY) and its dynamics over a longer time frame (14 years) in countries originating from the same political-economic system. The differences identified at this level have led to the conclusion that the state of WLB of employees from the V4 countries is only partly determined by systemic-historical conditions. WLB in the V4 countries reveals national-level differences and prompts further comparative research.
Keywords: I31; J7; E24; D6; 330; work-life balance (WLB); multiple factor analysis (MFA); WLB trajectories; Visegrad Group Countries (V4); international comparisons